2012
DOI: 10.1101/lm.028266.112
|View full text |Cite
|
Sign up to set email alerts
|

The medial dorsal thalamic nucleus and the medial prefrontal cortex of the rat function together to support associative recognition and recency but not item recognition

Abstract: In humans recognition memory deficits, a typical feature of diencephalic amnesia, have been tentatively linked to mediodorsal thalamic nucleus (MD) damage. Animal studies have occasionally investigated the role of the MD in single-item recognition, but have not systematically analyzed its involvement in other recognition memory processes. In Experiment 1 rats with bilateral excitotoxic lesions in the MD or the medial prefrontal cortex (mPFC) were tested in tasks that assessed single-item recognition (novel obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 50 publications
8
98
1
Order By: Relevance
“…MD or prefrontal damage indeed produce similar effects in recognition (Cross, Brown, Aggleton, & Warburton, 2012), or action-outcome association learning Corbit et al, 2003;Ostlund & Balleine, 2008;Parnaudeau et al, 2014;Tran-Tu-Yen, Marchand, Pape, Di Scala, & Coutureau, 2009 et al, 2013), we found no evidence for a deficit in reversal abilities. However, there have been some indications that MD lesions may produce greater deficits during reversal of a simple discrimination than during reversal of a conditional discrimination, as is the case in the present study (Chudasama et al, 2001).…”
Section: Discussion/conclusionsupporting
confidence: 44%
“…MD or prefrontal damage indeed produce similar effects in recognition (Cross, Brown, Aggleton, & Warburton, 2012), or action-outcome association learning Corbit et al, 2003;Ostlund & Balleine, 2008;Parnaudeau et al, 2014;Tran-Tu-Yen, Marchand, Pape, Di Scala, & Coutureau, 2009 et al, 2013), we found no evidence for a deficit in reversal abilities. However, there have been some indications that MD lesions may produce greater deficits during reversal of a simple discrimination than during reversal of a conditional discrimination, as is the case in the present study (Chudasama et al, 2001).…”
Section: Discussion/conclusionsupporting
confidence: 44%
“…Such a phenotype was also induced by bilateral lesions not only in the PFC, but also in the MD nuclei, suggesting a complex interplay between both brain regions. Further supporting the critical role of connections between the MD nuclei and PFC in recognition memory when the discriminations involve associative information, contralateral lesions in MD nuclei and the PFC, but not ipsilateral lesions, similarly abolish novelty discrimination in the object-inplace task (47). In addition, 5-HT 2A −/− mice, in which 5-HT 2A receptor expression was specifically restored in MD nuclei using a viral strategy, exhibited a similar performance as WT animals in the object-in-place task.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the mPFC and MD nuclei were found to cooperate within an integrated neural circuit to support associative learning, a key feature of episodic memory, and disruption of the thalamocortical pathway impaired learning of object-in-place associations (47). Furthermore, the temporal relationship of spike timing-dependent plasticity resembles typical features of associative learning (28).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, D 1 /D 5 blockade in either the mPFC or PRH had no effect on NOR, thus the memory impairments cannot be attributed to a general impairment of arousal or changes in locomotor activity. A number of studies demonstrate permanent or temporary lesions of the mPFC or specific catecholaminergic depletion within the mPFC does not affect NOR (Mitchell and Laiacona 1998;Hannesson et al 2004;Barker et al 2007;Nelson et al 2011;Cross et al 2012) suggesting that single item recognition does not depend on the mPFC. In contrast one study has shown that SCH23390 administration into the prelimbic cortex dose-dependently impaired NOR following a 5 min delay (Clausen et al 2011) and at present there is no clear reason for the discrepancy between this study and the present results, although the present study used a higher drug concentration (5 mM compared with 0.05-0.5 nM) and different strains of rats were used in the two studies.…”
mentioning
confidence: 99%